Biopsy-Proven Glomerulopathies in Romania: A 10-Year Nationwide Study - Andreea Covic; Mihai Onofriescu; Flaviu R. Bob; Cristina Căpușă; Irina-Draga Căruntu; Otilia Ciurea; Adrian Covic; Simona Giusca; Ina Kacso; Adelina Mihăescu; Andreea Niculescu; Bogdan Obrișcă; et al. (Life, 2025)
Glomerular diseases are a major cause of chronic kidney disease worldwide, yet epidemiological data from Eastern Europe, and Romania in particular, remain scarce. This study aimed to characterize the spectrum of biopsy-proven glomerulopathies in Romania through a multicenter national registry over a 10-year period. We retrospectively analyzed 4047 native kidney biopsies performed between 2014 and 2023 across four national nephrology reference centers. Patient demographics, clinical presentation, and histopathological diagnoses were collected and categorized into primary and secondary glomerular diseases, glomerulosclerosis, tubulointerstitial nephropathies, hereditary nephropathies, and vascular nephropathies. The mean patient age was 48 years, 54.8% were male, and 51.4% presented with nephrotic-range proteinuria. The most common primary glomerulopathies were membranous nephropathy (16.7%), immunoglobulin A nephropathy (15.6%), focal segmental glomerulosclerosis (8.8%), and membranoproliferative glomerulonephritis (10%). Among secondary glomerular diseases, lupus nephritis (9.3%), diabetic nephropathy (8.5%), and vasculitis (7.7%) were most frequent. Marked inter-center variability was observed, with a notably high prevalence of membranous nephropathy in Iași (31.1%). Over the study period, the incidence of focal segmental glomerulosclerosis increased while immunoglobulin A nephropathy declined. This study provides the first nationwide epidemiological assessment of biopsy-proven glomerular disease in Romania, revealing both similarities and distinctive differences compared to patterns reported in other European countries.